Assistance to Australian agriculture from Federation to World War II1. (1st August 2014) - Lloyd, Peter; MacLaren, Donald
<x xml:space="preserve">Abstract</x> This paper quantifies the levels of assistance received by producers of the major agricultural crops and animal products in Australia from Federation to the end of World War II. We outline the history of government assistance to the sector after Federation. Six measures of assistance are examined. Then the nominal rates of assistance from these measures are calculated for 20 agricultural products, 14 of which are classified as exportables and 6 as importables. From these product measures of assistance, we construct a series of the production‐weighted average nominal rate of assistance for the group of exportable products and for the group of importable products and for the whole sector. Our results show that, from the time of Federation, the pattern of assistance to the sector discriminated persistently and heavily against the exportable agricultural products.